Numerical simulation of a 3-D flow within a storage area hexagonal modular pavement systems - Rashid M.A.; Abustan I.; Hamzah M.O. (Institute of Physics Publishing, 2023)
This numerical study has been performed to predict the flow patterns and characteristics within a storage area Hexagonal Modular Pavement Systems. Throughout the design and planning period for future construction are increasingly integrating computational fluid dynamics (CFD) into the process. A commercially known software, FLOW-3D, is applied to numerically solve the Navier-stokes equations for solution domains which are separated into three regions with overlapping boundaries to efficiently accommodate the grid resolutions, namely the honeycomb shaped modular, gravel and combined honeycomb shaped modular with gravel fill. The filtration of the fluid within the interstices of a permeable pavement is evaluated by integrating the Reynolds Averaged Navier-Stokes equations (RANS) inside the voids rather than making use of the widespread porous media approach. In conclusion, the results from numerical simulation are generally well agreed with the existing data and flow information such as flow patterns at increased flow, discharge rate and pressure is obtained to be used for engineering design purpose. Overall, the potential for FLOW-3D to model various geometries and configurations appears great. It should be noted that CFD should not be considered a complete replacement for physical modelling; however, it can definitely be used as a supplementary tool throughout the pavement design process. Published under licence by IOP Publishing Ltd.